A Study of Hematological Changes in Dengue Patients at A Tertiary Care Hospital, Bhavnagar, Gujarat - Jethva, Vishva Narendrabhai; Thaker, Mayuri Vasudevbhai (Annals of Pathology and Laboratory Medicine, 2018)
Background: Dengue is one of the most common arthropod-borne viral (arboviral) illness in humans. It is transmitted by mosquitoes of the genes aedes-principally aedes aegypti. Present study focuses on the haematological changes in serologically proven dengue positive patients in tertiary care hospital. Methods: Retrospective observational study was conducted amongst NS1antigen/IgM dengue positive dengue patients in a tertiary care hospital for a period of 6 months.Complete hemogram of one hundred patients was studied and analysed. Result: Out of the 100 patients studied, 65% patients were in 12-30 years age groups and 75% were males. Leucopoenia was noticed in 36% of cases. Thrombocytopenia at presentation was seen in 94 % of cases. Raised liver serum transaminases, predominantly SGOT were found in 16 out of 20 patients. Conclusion: Fever associated with thrombocytopenia, leucopoenia and elevated liver transaminases should prompt a clinician on the possibility of dengue infection. Platelet transfusions have a little role in management of dengue patients.